(untitled) (Journal of Current and Advance Medical Research, 2019)
Diabetes Mellitus (DM), one of the most non-communicable diseases, is increasing day by day in an alarming way. More than 140 million people are suffering from diabetes throughout the world. It is not a single disease entity, but rather a group of metabolic disorders sharing the common underlying feature of hyperglycemia. Hyperglycemia in diabetes results from defects in insulin secretion, insulin action, or, most commonly, both. The chronic hyperglycemia and attendant metabolic deregulation may be associated with secondary damage in multiple organ systems, especially the kidneys, eyes, nerves, and blood vessels. The pathophysiology of diabetes is not fully elucidated. Insulin secretory dysfunction and insulin resistance or both is main candidate for this metabolic disorder, moreover various genetic and environmental factors may also involve in this process. Racial variations play also an important role as evidenced by various studies. However, the interrelationships between the molecular and metabolic mechanisms in these parameters contributing this life threatening disease still remain a mystery to the scientists. Journal of Current and Advance Medical Research 2019;6(1):59-63